Malaxis engelsii (Malaxidinae), a new species from the upper montane forest of the Atlantic Rainforest in southern Brazil - Santos, Thiago Faria dos
Malaxis engelsii is a newly discovered orchid found in the upper montane forests of the Atlantic Rainforest in Paraná, Brazil. This species is characterized by its small size, elliptic leaves, flowers with partially connate sepals at the base, trilobate lip with four cavities, and a longitudinal keel on the adaxial surface of the lip apex. A detailed description, photographs, drawings, and comparison with similar species, Malaxis cipoensis, M. sertulifera, and M. ybytus, are provided. Currently, it is classified according to the IUCN guidelines as "Endangered (EN)".